2014
DOI: 10.1371/journal.pone.0110244
|View full text |Cite
|
Sign up to set email alerts
|

Amygdalin Influences Bladder Cancer Cell Adhesion and Invasion In Vitro

Abstract: The cyanogenic diglucoside amygdalin, derived from Rosaceae kernels, is employed by many patients as an alternative anti-cancer treatment. However, whether amygdalin indeed acts as an anti-tumor agent is not clear. Metastasis blocking properties of amygdalin on bladder cancer cell lines was, therefore, investigated. Amygdalin (10 mg/ml) was applied to UMUC-3, TCCSUP or RT112 bladder cancer cells for 24 h or for 2 weeks. Tumor cell adhesion to vascular endothelium or to immobilized collagen as well as tumor cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 28 publications
2
26
0
Order By: Relevance
“…Moreover, our results showed that the amygdalin is efficiently induced to the inhibition of cell growth at ∼10 mg/ml concentration as reported in the previous studies (Shragg et al 1982;Chen et al 2013;Makarević et al 2014aMakarević et al , 2014b. However, we interestingly found that the normal somatic cells (MCR-5 fibroblasts) show considerable resistance to the cell growth and senescence at 10 mg/ml concentration of amygdalin.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Moreover, our results showed that the amygdalin is efficiently induced to the inhibition of cell growth at ∼10 mg/ml concentration as reported in the previous studies (Shragg et al 1982;Chen et al 2013;Makarević et al 2014aMakarević et al , 2014b. However, we interestingly found that the normal somatic cells (MCR-5 fibroblasts) show considerable resistance to the cell growth and senescence at 10 mg/ml concentration of amygdalin.…”
Section: Discussionsupporting
confidence: 90%
“…Cell growth and proliferation were dose-dependently induced in UMUC-3, RT112 and TCCSUP bladder cancer cell lines treated with amygdalin, resulting in arrest of cell cycle progression by down-regulation of cdk2 and cyclin A (Makarević et al 2014a), and amygdalin treatment to SNU-C4 human colon cancer cells also displayed anticancer effect via down-regulation of cell cycle-related genes, implying that the amygdalin compound is induced to incomplete DNA synthesis (Park et al 2005). Furthermore, it has been demonstrated that apoptosis is induced by up-regulating caspase-3 activity and pro-apoptotic Bax protein, whereas down-regulating anti-apoptotic protein Bcl-2 in the amygdalin-treated HeLa cells (Chen et al 2013), human DU145 and LNCaP prostate cancer cells (Chang et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then we evaluated the antitumor effects of amygdalin in bladder cancer, which ranked the first in the incidence of genitourinary tumors in China . Makarević et al detected tumor cell adhesion to vascular endothelial cells or migration of immobilized collagen and tumor cells, and observed the effects of amygdalin on integrin α and β subtypes, ILK (integrin‐linked kinase) and FAK (focal‐adhesion kinase) after treatment of bladder cancer UMUC‐3 and RT112 cells with amygdalin at a dose of 10 mg/mL for 24 hours or 48 hours; they knocked down integrin to evaluate the impact of integrin knockdown on cell migration and adhesion, and found that adhesion and migration of UMUC‐3 and RT112 cells were inhibited after amygdalin treatment, and at the time the expressions of integrin α and β subtypes, ILK and FAK were all decreased.…”
Section: Recent Updates In Research Of the Anti‐tumor Effect Of Amygdmentioning
confidence: 99%
“…Amygdalin induced apoptosis of HeLa cervical cancer cells mediated by endogenous mitochondrial pathway ( Chen et al ., 2013 ). A recent study showed that amygdalin reduced adhesion and migration of UMUC-3 and RT112 bladder cancer cells through activation of focal adhesion kinase (FAK) and modulation of β1 integrin ( Makarević et al ., 2014 ).…”
Section: Introductionmentioning
confidence: 99%